Response Evaluation on Single Common and Uncommon EGFR Mutation on First-Generation EGFR-TKI Therapy in NSCLC Patients - Rena Arusita Maranatha1 , Laksmi Wulandari2 , Gatot Soegiarto3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: To compare the response of first-generation EGFR-TKI (epidermal growth factor receptortyrosine kinase inhibitors) in non-small cell lung cancer (NSCLC) patients with single common anduncommon EGFR mutation.Methods: Patients were divided into two groups, the uncommon (exon 21 L861Q, exon 18 G719X, exon18 delE709) and common EGFR mutation group (exon 19 deletion, exon 21 L858R). Health-related qualityof life (HRQOL) using EuroQol EQ-5D® questionnaire, body weight, performance status (PS), ResponseEvaluation Criteria in Solid Tumors (RECIST) on chest CT, progression-free survival (PFS) and overallsurvival (OS) was recorded during TKI therapy.Results: The value of HRQOL was stable and PS was constant in both groups, body weight was constantin uncommon group (42.1%) and increased in common group (44.1%; p=0.165). The uncommon groupshowed mostly progressive disease in RECIST (47.4%) while the common group showed mostly partialresponse (42.2%; p=0.007). PFS in the uncommon group was 4 (2.0-6.0) months and 7.0 (2.0-21.0) monthsin the common group (p=0.001). OS in the uncommon and common group were 4.00±1.71 months and10.00±6.94 months (p<0.001), respectively.Conclusion: NSCLC patients with common EGFR mutations showed a better response and survival ratecompared to uncommon EGFR mutations on first-generation TKI therapy.